The Nature of Beauty - Woodbury, Virginia Garton; Bucks County Intermediate Unit 22, Doylestown, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
One in a series of instructional units designed for gifted students, the booklet focuses on the arts in Greece, Rome, and the Medieval period. Narrative information on Greek pottery, sculpture, architecture, music, and dance is followed by lists of suggested activities for students and reference lists of texts and media. A similar unit on the Romans deals with architecture, sculpture, painting, music, and dance. The third unit, on the Medieval Period, reviews aspects of Byzantine art, the Early Middle Ages, Romanesque art, the Gothic period, music, and dance. Lists of references, including audiovisual suggestions, conclude each unit. (CL)
ERIC Note: Prepared by the Special Education Division. For related documents, see EC 171 144-152. See note to EC 171 144.
Teachers.
Practitioners.
Microfiche.
Keywords: Aesthetic Education; Art History; Fine Arts; Gifted; Greek Civilization; History; Medieval History; Secondary Education; Units of Study; Roman Civilization; Guides, Classroom -- Teacher